The Linked Factor of Customer Satisfaction and Loyalty in F&B Industry: A Study of Operational Performance Factor - Cheng, Yen Er; Cheah, Yun Yee; Jimenez, Dana Valentina Rojas; Chen, Yuxin; Chen, Yifei (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
The focus of this research is to investigate how operational performance affects customer satisfaction and loyalty in the food and beverage industry. Starbucks has been selected as this research object. Conducting a survey and referring to other studies of journals and articles to support the assisting data are the research methods employed. According to the research results, 71 % of respondents are pleased with current Starbucks services and products. The studies also revealed that the majority of customers had heard of Starbucks on social media. The study’s findings reveal that operation success is significantly linked to customer satisfaction. Customer satisfaction has been described as a significant mediator between service quality and customer loyalty. Having a clear understanding of the hypothesized relationship in the study encourages Starbucks to figure out the best action to gain or increase customer loyalty by providing good service quality to build a loyal customer base and customer satisfaction.